Fruit sampling methods to quantify calcium and magnesium contents to predict bitter pit development in 'Fuji' apple: A multivariate approach - Do Amarante C.V.T.* (2013)
Bitter pit (BP) is a physiological disorder in apple commonly associated with high Mg/Ca ratio in fruit tissue. This work was carried out to identify the best fruit tissue sampling method for Ca and Mg assessment to discriminate 'Fuji' apples regarding the occurrence of BP. After six months under controlled atmosphere storage (2.0kPa O2+0.5kPa CO2, at 0.5°C/90-95% RH), fruit without or with BP were submitted to Ca and Mg analysis (mgkg-1 of fresh weight) in the total fraction (TF) of peel+flesh, and in the TF and soluble fraction (SF) of flesh or peel tissues. For the peel+flesh, a wedge-shaped segment was cut longitudinally from the fruit (with 1cm wide at the equatorial region), discarding the core tissue. For individual sampling of the peel (thickness of 0-2mm) or flesh (thickness of 2-8mm), the fruit were cut along the equatorial region, so that only the distal end was used. In this portion of the fruit, Ca and Mg contents were higher in the peel than in the flesh in the TF, and lower in the peel than in the flesh in the SF, while the Mg/Ca ratios in TF and SF fractions were higher in the flesh than in the peel, regardless the occurrence of BP. Calcium and Mg contents in the SF relative to the TF were very low in both peel and flesh tissues. Calcium in the SF represented 0.36% and 2.79% of its content in the TF for peel and flesh, respectively. Magnesium content in the SF represented 0.70% and 3.74% of that in the TF for peel and flesh, respectively. Fruit without BP showed higher Ca content and lower Mg/Ca ratio in the TF of peel+flesh, peel or flesh, and in the SF of peel or flesh, compared to fruit with BP. Fruit without BP also showed a higher percentage of Ca in the SF in relation to TF in the peel (0.42%) compared to fruit with BP (0.31%). Fruit without BP also showed lower Mg content in TF of peel+flesh and peel, and in the SF of the flesh. There was no difference between fruit with and without BP only for Mg contents in TF of the flesh and SF of the peel. The canonical discriminant analysis showed that the Mg/Ca ratio in the SF of the peel tissue at the distal end of the fruit provides the best method to discriminate fruit without and with BP, which can be potentially used as a tool to predict BP development in 'Fuji' apples. © 2013 Elsevier B.V.